Terahertz transmission through TaAs single crystals in simultaneously applied magnetic and electric fields: Possible optical signatures of the chiral anomaly in a Weyl semimetal - Felix Hütt; Dmytro Kamenskyi; David Neubauer; Chandra Shekhar; Claudia Felser; Martin Dressel; Artem V. Pronin (Results in Physics, 2019)
We report optical transmission measurements through a single crystal of the Weyl semimetal TaAs at terahertz frequencies. The measurements were performed at T=1.6 K using intense coherent light from a free-electron laser in high magnetic fields. We detected small but measurable changes in the sample’s transparency upon applying dc voltage (current) to the sample. In a constant magnetic field, the sign of the transmission change depends on the current direction. The effect disappears in zero magnetic field. These observations are qualitatively consistent with theory predictions for optical signatures of the chiral anomaly in a Weyl semimetal. Keywords: Topological semimetals, Weyl fermions, Chiral anomaly